B.C.’s Occupational Vision Program - Cox, B D; Little, T J (Canadian Journal of Optometry, 1983)
The BCOA's occupational vision committee has adopted the model set forth by the national committee and, with a few minor adjustments, has created a program that is catching the eye of safety personnel around the province.